Spermatological characters of Acanthobothrium crassicolle Wedl, 1855 (Tetraphyllidea, Onchobothriidae), a parasite of the common stingray Dasyatis pastinaca - Marigo, Adji Mama (2011)
We describe the spermiogenesis process and the ultrastructural characters of the spermatozoon of Acanthobothrium crassicolle by means of transmission electron microscopy, including cytochemical analysis for glycogen. Spermiogenesis in A.crassicolle begins with the formation of the differentiation zone that contains two centrioles associated with striated rootlets and an intercentriolar body. The latter is formed by one electron-dense layer. The centrioles develop into two free flagella that first grow orthogonally to a median cytoplasmic process and then undergo flagellar rotation becoming parallel to that median cytoplasmic process. After flagellar rotation only one of the flagella completes its growth and both short and long flagella undergo proximodistal fusion with the median cytoplasmic process. In the final stages of spermiogenesis, the nucleus becomes filiform and migrates into the spermatid body. Later, the ring of arched membranes constricts and the spermatozoon is liberated from the residual cytoplasm. The ultrastructural organization of the spermatozoon of A.crassicollefollows the general pattern of spermatozoa of the other Tetraphyllidea-Onchobothriidae species, but exhibits some differences. It is filiform, tapered at both extremities and lacks mitochondrion. It contains two axonemes of unequal length showing the 9 + “1” pattern of Trepaxonemata, a nucleus, parallel cortical microtubules and electron-dense granules of glycogen. The anterior extremity of the male gamete contains a single crested body surrounding a thin and long apical cone. This type of apical cone has never been described in a tetraphyllidean spermatozoon. Another particularity is the presence of a single electron-dense microtubule at the vertex of the crested body.